2004
DOI: 10.1210/en.2004-0144
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Corticotropin-Releasing Hormone and Urotensin I Precursor Genes in the Caudal Neurosecretory System of the Euryhaline Flounder (Platichthys flesus): A Possible Shared Role in Peripheral Regulation

Abstract: CRH and urotensin I (UI) are neuroendocrine peptides that belong to the superfamily of corticotropin-releasing factors. In mammals, these peptides regulate the stress response and other central nervous system functions, whereas in fish an involvement for UI in osmoregulation has also been suggested. We have identified, characterized, and localized the genes encoding these peptides in a unique fish neuroendocrine organ, the caudal neurosecretory system (CNSS). The CRH and UI precursors, isolated from a European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 39 publications
7
59
1
2
Order By: Relevance
“…Similar to the expression pattern of CRF as described above, the POA and the CNSS are among the principal sites of UI expression in the CNS. While several studies have previously identified the CNSS as a major site of UI expression in teleosts (Winter et al 2000, Lu et al 2004, the POA was only recently recognized in zebrafish as a site of CRF and UI co-expression (Alderman & Bernier 2007). We also identified the midbrain as a primary site of UI gene expression in the CNS of rainbow trout.…”
Section: Cns Distribution Of Crf and Ui Gene Expressionmentioning
confidence: 74%
See 4 more Smart Citations
“…Similar to the expression pattern of CRF as described above, the POA and the CNSS are among the principal sites of UI expression in the CNS. While several studies have previously identified the CNSS as a major site of UI expression in teleosts (Winter et al 2000, Lu et al 2004, the POA was only recently recognized in zebrafish as a site of CRF and UI co-expression (Alderman & Bernier 2007). We also identified the midbrain as a primary site of UI gene expression in the CNS of rainbow trout.…”
Section: Cns Distribution Of Crf and Ui Gene Expressionmentioning
confidence: 74%
“…To what extent the CNS pattern of CRF gene expression observed in rainbow trout is characteristic of other teleosts is not known. To date, in the only other teleost species where CRF expression has been localized to the CNSS, the flounder (Lu et al 2004), a quantitative distribution pattern has not been performed.…”
Section: Cns Distribution Of Crf and Ui Gene Expressionmentioning
confidence: 99%
See 3 more Smart Citations